(untitled) (Texas Journal of Medical Science, 2022)
The connection between cardiac and renal pathology has long attracted the attention of both cardiologists and nephrologists. The kidneys, the glomeruli of which are part of the microcirculatory system of the body, affect the formation of cardiovascular pathology, at the same time they themselves are involved in the pathological process in various cardiovascular diseases (CVD). For heart and kidney diseases, there are a number of common risk factors (FR): arterial hypertension (AH), diabetes mellitus (DM), obesity, dyslipidemia, etc. In patients with hypertension, coronary heart disease (CHD), especially in combination with diabetes and chronic heart failure (CHF), renal dysfunction is quite common. At the same time, impaired renal function is an important independent factor in the development of such cardiovascular complications as myocardial infarction (MI), heart failure, fatal arrhythmias. Renal dysfunction is associated with a more frequent development of complications and death in patients with acute coronary syndrome, including during thrombolytic therapy, and a third of patients who have undergone MI are diagnosed with stage 3-5 CKD. CKD is recognized as the equivalent of coronary heart disease in terms of the risk of cardiovascular complications. The decrease in GFR in CHF is as significant as the value of the left ventricular ejection fraction or the functional class of CHF. Such a connection of damage to the cardiovascular system and kidneys allowed in 2008 to develop and adopt the concept of cardiorenal relationships, while five types of cardiorenal syndrome were identified depending on the type of lesion (acute or chronic) and the initiator organ: type 1 – acute heart failure leads to acute renal damage; type 2 – chronic cardiac insufficiency leads to chronic renal damage; type 3 – acute renal damage leads to acute myocardial dysfunction; type 4 – chronic kidney disease leads to CHF; type 5 – simultaneous kidney and heart damage in systemic diseases, including vasculitis, DM, amyloidosis, sepsis